Evaluating the Effect of a Health Humanities Course on Undergraduate Perceptions of LGBT Health Disparities - Chow, Donna Tung (My University, 2021)
Purpose: To assess how undergraduates’ perceptions of the health disparities affecting the LGBT community can change through exposure to a health humanities course dedicated to contextualizing the social health determinants within the LGBT community. Study Design: This qualitative study used a pre- and post-test design to assess changes in participant perceptions of the health disparities affecting the LGBT community. The goal of the study was to obtain any key changes in student perceptions of LGBT health or the LGBT community after taking a health humanities course dedicated to contextualizing the social health determinants within the LGBT community using art, theatre, and music as a framework. Methods: Undergraduates enrolled in HSC390: LGBT Communities & Health at California State University, East Bay, and consented to participate in the study, were asked to complete a 9-item questionnaire at two timepoints: before and after the course. Twenty participants responded to the questionnaire prior to the intervention and 18 completed the questionnaire post- intervention. The responses were analyzed using a thematic analysis to determine whether undergraduates’ perceptions of the health disparities affecting the LGBT community changed due to exposure to the intervention. Results: Overall, identified themes both before and after the course, indicated that undergraduate perceptions of the health disparities within the LGBT community remained consistent. However, changes within the themes, following HSC390, indicated the 17-week course helped the undergraduates better contextualize LGBT issues and gain a more in depth understanding of the health disparities within the LGBT community. Conclusion: An undergraduate health humanities course dedicated to contextualizing the social health determinants via art, theatre, and music can impact student perceptions of the health disparities affecting the LGBT community.
Thesis (Master's)--University of Washington, 2020
Keywords: Public health; Health services